Burden of non‐alcoholic fatty liver disease in Australia. (28th May 2018) - Mahady, Suzanne E; Adams, Leon A
Abstract: Non‐alcoholic fatty liver disease (NAFLD) is the commonest cause of chronic liver disease in the Australian population, although precise estimates of prevalence are lacking. NAFLD may progress to liver fibrosis, cirrhosis, decompensated liver disease, and liver cancer and is becoming an increasingly common indication for liver transplantation in Australia and New Zealand. There is an extrahepatic burden of NAFLD extending beyond the liver, which is manifested by an increased risk of developing cardiovascular disease, diabetes, and chronic renal impairment, all of which are common causes of morbidity in the Australian population. Early recognition of those patients at high risk of developing advanced liver disease is essential in order to target those who will benefit from intensive lifestyle modification. In this review, we present data on the epidemiology of NAFLD within Australia, its associated health burden in terms of hepatic and extrahepatic complications, common clinical presentations, and indications for treatment. We also propose a research agenda that highlights knowledge needed to improve diagnosis and management specific to the Australian context.